Анализа корелације нивоа експресије сировинског молекула за адхезију ендотелних ћелија-1 и протеина сиртуин 1 код акутног респираторног дистрес синдрома: Серумски молекул за адхезију ендотелних ћелија-1 и протеин сиртуин 1 код АРДС-а - Peng, Can; Sun, Zhigang; Liu, Yanyan; Zhao, Hao (Journal of Medical Biochemistry, 2025)
Objective: To investigate the relationships among serum silencing information regulator 2-related enzyme 1 (SIRT1) expression levels, endothelial cell-specific molecule-1 (ESM-1), and fibroblast growth factor-21 (FGF21) and treatment results in patients with acute respiratory distress syndrome (ARDS) associated with sepsis.Methods: A total of 140 patients with sepsis-related ARDS were selected and divided into a good outcome group of 96 patients and a poor outcome group of 44 patients according to the treatment outcome. The levels of serum SIRT1, ESM-1 and FGF21 were compared between the two groups; the correlations between serum SIRT1, ESM-1, and FGF21 and the severity of the disease as well as the treatment outcome were analyzed; and the predictive value of serum SIRT1, ESM-1 and FGF21 for treatment outcomes was evaluated.Results: Compared to the group with a favorable outcome, the bad outcome group's serum SIRT1 level was lower, while the ESM-1 and FGF21 levels were significantly greater than those in the good outcome group (P
Keywords: Сепсис-асоциран синдром акутног респираторног дистреса; Ензим 1 повезан са фактором регулације информација 2 у тишини; Ендотелска ћелија-специфични молекул-1; Исход лечења; Придружени фактор раста фибробласта-21